PENGARUH INVESTASI, TENAGA KERJA, DAN PENGELUARAN PEMERINTAH TERHADAP KEMISKINAN DI SUMATERA UTARA PADA TAHUN 2006-2020 - Febby Irma Fazaryani; Reza Juanda (JURNAL EKONOMIKA INDONESIA, 2022)
This study examined and analyzed the effect of Investment, Labor, and Government Expenditure on Poverty in North Sumatra and used secondary data from 2006 to 2020. The regression model used was a multiple linear regression model using the Ordinary Least Square (OLS) method and classical assumption tests, consisting of a normality test, multicollinearity test, autocorrelation test, and heteroscedasticity test. The regression tool used was the Eviews 10. According to the result indicated that the realization of investment and the realization of government expenditures did not and insignificantly affect the number of poor people in North Sumatra, and labor negatively and significantly affected the number of poor people in North Sumatra. Simultaneously, the realization of investment, labor, and government expenditure influenced the number of poor people in North Sumatra. The coefficient of determination test results showed a relationship between the independent and dependent variables of 66.55%, and the rest of 33.44% was influenced by other variables outside this study.